The influence of dark chocolate consumption on the microbial population in the oral cavity - Mișcă Corina; Raba Diana; Dumbravă Delia; Moldovan Camelia; Borozan Aurica Breica; Popa Mirela; Rinovetz Alexandru; David Ioan (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2023)
This study was initiated at the Faculty of Food Engineering within the Mihai I University of Life Sciences in Timișoara, with the aim of identifying the effect of dark chocolate with a high concentration of cocoa on the microbial population in the oral cavity, which facilitates the formation of dental plaque, tartar and implicitly the appearance of dental caries. The specialized literature directed us to this study and we wanted to highlight the presence of microorganisms that can be isolated from the oral cavity and the effectiveness of this treatment - the consumption of dark chocolate after meals, in small quantities. The methods for isolating microorganisms were the classic ones imposed by the standards. The results obtained confirmed the bactericidal effect of dark chocolate with a high cocoa content. In conclusion, the consumption of a quantity of 10 grams of dark chocolate, after the meal exerted a beneficial effect on oral hygiene, by reducing the number of acidogenic microorganisms.